Hypertension and intracerebral hemorrhage recurrence among white, black, and Hispanic individuals. (3rd July 2018) - Rodriguez-Torres, Axana; Murphy, Meredith; Kourkoulis, Christina; Schwab, Kristin; Ayres, Alison M.; Moomaw, Charles J.; Young Kwon, Soo; Berthaud, Jimmy V.; Gurol, M. Edip; Greenberg, Steven M.; Viswanathan, Anand; Anderson, Christopher D.; et al.
Abstract : Objective: To clarify whether recurrence risk for intracerebral hemorrhage (ICH) is higher among black and Hispanic individuals and whether this disparity is attributable to differences in blood pressure (BP) measurements and their variability. Methods: We analyzed data from survivors of primary ICH enrolled in 2 separate studies: (1) the longitudinal study conducted at Massachusetts General Hospital (n = 759), and (2) the ERICH (Ethnic/Racial Variations of Intracerebral Hemorrhage) study (n = 1, 532). Participants underwent structured interview at enrollment (including self-report of race/ethnicity) and were followed longitudinally via phone calls and review of medical records. We captured systolic BP (SBP) and diastolic BP measurements, and quantified variability as SBP and diastolic BP variation coefficients. We used multivariable (Cox regression) survival analysis to identify risk factors for ICH recurrence. Results: We followed 2, 291 ICH survivors (1, 121 white, 529 black, 605 Hispanic, and 36 of other race/ethnicity). Both black and Hispanic patients displayed higher SBP during follow-up ( p < 0.05). Black participants also displayed greater SBP variability during follow-up ( p = 0.032). In univariable analyses, black and Hispanic patients were at higher ICH recurrence risk ( p < 0.05). After adjusting for BP measurements and their variability, both Hispanic (hazard ratio = 1.51, 95% confidence interval 1.14–2.00, p = 0.004) and black (hazard ratio = 1.98, 95% confidence interval 1.36–2.86, p < 0.001) patients remained at higher risk of ICH recurrence. Conclusion: Black and Hispanic patients are at higher risk of ICH recurrence; hypertension severity (average BP and its variability) does not fully account for this finding. Additional studies will be required to further elucidate determinants for this health disparity.